Volumetric and Impact-Oriented Water Footprint of Agricultural Crops: A Review. (November 2021) - Deepa, R.; Anandhi, Aavudai; Alhashim, R.
Graphical abstract: Highlights: Literature review was done on water footprint and freshwater ecotoxicity indicator of agricultural crops. Emergence of eutrophication and ecotoxicity water footprints -impact based water footprints. In 64% of the studies, USEtox and ReCiPe methods are used for impact assessments. Nearly 60% of the studies use water consumption as its goal and 80% used the WFP assessment methodology. Abstract: The Water Footprint (WFP) is an estimate of freshwater utilization in food production and its impacts on water resources by individuals, communities and industries. It is partitioned into green component that denotes rain water use, blue, ground and surface water, and grey, water used to assimilate the pollutant. In this study we try to review the current understanding of WFP concept from a volumetric and impact-oriented perspective. A meta -analysis was done from published peer reviewed literature related to the agricultural WFP of crops from google scholar database for the time frame 2006 to 2020. The results from the volumetric review shows the goal of nearly 60% of the studies is on the water consumption of crops, 62% of the studies focused on the three components of WFP and 80% of them used the WFP assessment methodology for its accounting. The progress of WFP research illustrates water scarcity or depletion is well explored compared to water degradation. However, after the emergence of ISO 14046, a stand-alone Life Cycle Assessment (LCA) method, scientific community started focusing on sustainability/impact assessment from a water degradation (eutrophication, ecotoxicity footprints) outlook. From the impact-oriented review on freshwater ecotoxicity, it is understood that majority of the studies use compartment models such us USEtox and ReCiPe methods for impact assessments using an egalitarian time frame. This review suggests the potential factors influencing the water impact indicators and guidance for comprehensive WFP assessment. Besides, future WFP assessments may consider the drivers of water, food and energy security for a complete understanding for water resource and environmental management decisions